2000
DOI: 10.1634/theoncologist.5-6-510
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Cycle

Abstract: The Oncologist Fundamentals of Cancer MedicineThe cell cycle is a highly ordered process that results in the duplication and transmission of genetic information from one cell generation to the next. During the process DNA must be accurately replicated and identical chromosomal copies distributed to two daughter cells. The cell cycle is divided into discrete phases: G 1 (gap 1) is the interval or gap between mitosis (M phase) and DNA synthesis (S phase). During G 1 the cell is subject to stimulation by extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 0 publications
2
53
0
Order By: Relevance
“…The proliferative effects of CD1 relate to its control of G 1 transition in specific cell types (Arnold et al, 1991), and although it functions primarily by forming active complexes with CDK4 (Israels and Israels, 2000), CD1 can also act via mechanisms that are independent of CDK4 (Zwijsen et al, 1997;Knudsen et al, 1999;Bienvenu et al, 2001). Elevated CD1 in tumours can be achieved through different mechanisms including deregulated gene expression, mutations or amplifications (Weinberg, 1995).…”
Section: Brn-3b Is Bound To Cd1 Promoter In Intact Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proliferative effects of CD1 relate to its control of G 1 transition in specific cell types (Arnold et al, 1991), and although it functions primarily by forming active complexes with CDK4 (Israels and Israels, 2000), CD1 can also act via mechanisms that are independent of CDK4 (Zwijsen et al, 1997;Knudsen et al, 1999;Bienvenu et al, 2001). Elevated CD1 in tumours can be achieved through different mechanisms including deregulated gene expression, mutations or amplifications (Weinberg, 1995).…”
Section: Brn-3b Is Bound To Cd1 Promoter In Intact Cellsmentioning
confidence: 99%
“…CDK4 protein controls G 1 transition in cells as they progress through the cell cycle (Arnold et al, 1991) by associating with regulatory partners such as cyclin D1 (CD1) (also referered to as PRAD1, CCND1) (Motokura et al, 1991) to phosphorylate specific substrates such as retinoblastoma protein (Israels and Israels, 2000). However, whereas CDK4 is inhibited by its association with inhibitory protein such as p21 cip1/waf1 , the regulatory cyclin subunits are regulated at the level of expression and by protein stability as cells progress through the cell cycle (Guo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of p27 induces G1 arrest (Sherr, 2000). To permit hyperphosphorylation of pRb and cell-cycle progression, the inhibitory influence of p27 is removed through hyperphosphorylation, ubiquitination and destruction within the proteasome (Vlach et al, 1997;Israels and Israels, 2000). Owing to the high signal levels of total pRb, phospho-pRb, p27 and phospho-p27 found in the buccal mucosa in Study A, and the fact that the expression and activation of these cell-cycle proteins appeared relatively tightly controlled, with the nuclear signal being largely 'on or off' (Figure 2B -E) allowing easier automated counting, we chose to explore these markers in more detail in Study B.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, various studies suggested that caspase-8 is not only activated in the death receptor pathway, but can be also activated independently of death receptors. 26) In these previous studies, caspase-8 activation was found to be triggered by a caspase-3-mediated feedback amplification loop, and caspase-8 was proposed to act as an executioner caspase, rather than as an initiator caspase, in the death receptor-independent activation pathway. In our study, IPA did not influence the protein levels of Fas and TNFR1 (data not shown).…”
Section: Fig 4 Effect Of Ipa On Er Stress-mediated Apoptosis In Helmentioning
confidence: 98%